Keadaan Umum Alat Tangkap Ikan di Kelurahan Makawidey Kecamatan Aertembaga Kota Bitung - Juando Prasetya Roat; Lusia Manu (Universitas Sam Ratulangi, 2021)
ABSTRACTFishery is an economic activity that utilizes resources in fisheries by using science and technology for human welfare by optimizing and maintaining the productivity of fishery resources and fisheries sustainability (Yuniardi, 2011). This field work practice aims to (1) Know the general condition of capture fisheries in Makawidey Village (2) Present written information about the general condition of capture fisheries in Makawidey Village (3) Improve student work abilities in collecting capture fisheries information (4) Train students to preparation of field work practice reports. The data collection method is carried out through a survey which is based on the descriptive method. Data collection can be obtained directly from fishermen with direct interviews and written information from the local government. Makawidey Village is located in the city of Bitung with a population of 1393 people, where most of the population works as fishermen, amounting to 192 (73.84). The area of Makawide Village is 110 Ha consisting of residential areas, plantations, protected forests and state land. The fishing gear used by purse seines, soma dampar, noru fishing rods with the dominant catch is selar